The Concept of Digital Citizenship in the Schools of Saudi Arabia - Alzahrani, Ahmed (My University, 2019)
This research seeks to know the spread of the concept of digital citizenship among school students in Saudi Arabia. Literary reviews have shown the importance of the concept of digital citizenship among members of society as a whole, and the youth in particular. The exploratory study carried out by the researcher among high school students in the Kingdom of Saudi Arabia has also revealed the importance of digital citizenship. It was found that 81.3% of the participants in the survey did not know the concept of digital citizenship (Al-Fawaz, 2018). Therefore, the researcher has prepared many programs and activities to spread the concept of digital citizenship between students and the school community. A special training kit has been developed to train teachers and supervisors so that they can transfer the principles and elements of digital citizenship to the school community. A web site explaining the concept of digital citizenship was also designed by the researcher. In addition, special programs and activities for students will be implemented during the academic year in coordination with the centers of activity in the education departments. A proposal will be made to the Ministry of Education to include lessons on digital citizenship in the computer curriculum or secondary life skills curriculum. To measure the impact of these activities and programs on the spread of the concept of digital citizenship, a descriptive study will be conducted on secondary students and the data will be collected and analyzed statistically. It is important to know the strengths of activities and programs and to develop them. This researcher will investigate that the impact of these programs and activities will be positive on the target audience and thus increase awareness of the importance of digital citizenship.
Keywords: Digital Citizenship; Digital Societies; Digital Communication; Education